2003
DOI: 10.1159/000067863
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Vascular Access Dysfunction: From Pathophysiology to Novel Therapies

Abstract: Hemodialysis vascular access dysfunction is a major cause of morbidity and hospitalization in the hemodialysis population at a cost of over USD 1 billion per annum. Most hemodialysis grafts fail due to a venous stenosis (venous neointimal hyperplasia) which then results in thrombosis of the graft. Despite the magnitude of the clinical problem there are currently no effective therapies for this condition. The current review (a) describes the pathogenesis and pathology of venous stenosis in dialysis access graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 90 publications
1
85
0
5
Order By: Relevance
“…[1][2][3][4] The present study is the first to evaluate a gene therapy approach for the treatment of AV PTFE graft failure in a clinically relevant large-animal model. Histological assessment showed that adenovirus-mediated expression of ␤ARKct significantly reduced venous neointimal hyperplasia at the vein/graft anastomosis site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The present study is the first to evaluate a gene therapy approach for the treatment of AV PTFE graft failure in a clinically relevant large-animal model. Histological assessment showed that adenovirus-mediated expression of ␤ARKct significantly reduced venous neointimal hyperplasia at the vein/graft anastomosis site.…”
Section: Discussionmentioning
confidence: 99%
“…3 Intimal hyperplasia at the venous anastomosis is the primary cause of thrombosis and consequent vascular access dysfunction of AV PTFE hemodialysis grafts. [3][4][5] Despite the magnitude of the problem, there are currently no effective therapies for the prevention or treatment of venous intimal hyperplasia in PTFE grafts in these patients.…”
mentioning
confidence: 99%
“…According to the "traditional theory" of neointimal hyperplasia, endothelial and smooth muscle injury results in the migration of smooth muscle cells and myofibroblasts from the media into the intima, where they proliferate and form the lesion of venous neointimal hyperplasia. This process of injury followed by migration and proliferation is orchestrated by a large number of mediators, which include the cell-cycle regulators (p27 and p16, retinoblastoma protein, p38 mitogen-activated protein kinase); cytokines (PDGF, basic fibroblast growth factor, and TNF-␣); chemokines (monocyte chemoattractant protein-1 and RANTES); vasoactive molecules (nitric oxide [NO] and endothelin); adhesion molecules (intercellular adhesion molecule-1 and P-selectin); and molecules such as osteopontin, apolipoprotein E, matrix metalloproteinase-2, and human hepatocyte growth factor (24). It should be emphasized, however, that most of this information is derived from arterial angioplasty models rather than from vascular (venous) anastomosis models.…”
Section: Pathogenesis Of Avf and Ptfe Graft Failurementioning
confidence: 99%
“…This latter parameter is a good indicator of the amount of vascular or adventitial remodeling. Adapted from reference (24). multiple cell types (fibroblasts, myofibroblasts, and smooth muscle cells) instead of only the differentiated contractile smooth muscle cell.…”
Section: Alternative Origins For Neointimal Cells (Adventitia and Bonmentioning
confidence: 99%
“…The vast majority of arteriovenous (AV) access failure is caused by thrombosis, secondary to disproportionate intimal hyperplasia and impaired outward remodeling of the venous outflow tract (5)(6)(7)(8). The stimuli responsible for the localized intimal hyperplastic response in the venous outflow tract are multifactorial and include hemodynamic factors such as turbulent flow, the prothrombotic environment that results from endothelial damage, as well as vascular inflammation (9).…”
Section: Introductionmentioning
confidence: 99%